Pressure and Opportunity on Financial Statement Fraud with Political Connection as a Moderating Variable - Sumara Aslira; Grahita Chandrarin; Diana Zuhroh (AFRE (Accounting and Financial Review), 2024)
This research aims to examine and analyze the influence of pressure and oppor-tunity on financial statement fraud with political connection as a moderating va-riable, and is expected to assist stakeholders in decision-making. One way to detect financial statement fraud is by using the Altman Z-Score analy-sis, which consists of three measurement variables to generate a financial state-ment fraud score. The sample used in this study consists of 92 companies from a population of 147 companies in the consumer cyclical sector listed on the Indonesia Stock Exchange from 2019-2022, with a total sample of 368 companies. The type of this research is quantitative research, and the sampling technique used is purposive sampling. The ana-lysis used is moderate regression ana-lysis. This study shows that pressure has a significant relationship with financial statement fraud, while opportunity does not affect the potential for financial statement fraud. Political connection can effectively moderate pressure in relation to financial statement fraud, but it cannot moderate opportunity in relation to financial statement fraud. JEL Classification: G34, M42, C38 DOI: https://doi.org/10.26905/afr.v7i3.14468